Heart Rate Variability is Related to Disease Severity in Children and Young Adults with Pulmonary Hypertension - Latus, Heiner; Bandorski, Dirk; Rink, Friederike; Tiede, Henning; Siaplaouras, Jannos; Ghofrani, Ardeschir; Seeger, Werner; Schranz, Dietmar; Apitz, Christian (Frontiers in Pediatrics, 2015)
BACKGROUND: Pulmonary hypertension (PH) is frequently associated with an increase in sympathetic tone. This may adversely affect cardiac autonomic control. Knowledge about the clinical impact of autonomic dysfunction in patients with PH is limited. We aimed to assess whether parameters of heart rate variability (HRV) are related to disease severity in children with PH. METHODS: Parameters of HRV [SDNN = standard deviation of normal-to-normal intervals, and SDANN = standard deviation of mean values for normal-to-normal intervals over 5 min] were determined from Holter electrocardiograms of 17 patients with PH without active intracardial shunt (10 female, mean age 12.8 ±8.7 years). Patients were allocated to 2 groups according to their disease severity: patients with moderate PH (ratio of pulmonary to systemic arterial pressure (PAP/SAP ratio) <0.75) (n=11), patients with severe PH (PAP/SAP ratio >0.75) (n=6). An additional group of 5 adolescents with Eisenmenger syndrome (PAP/SAP ratio 1.13±0.36) was included. RESULTS: Children with severe PH had significantly lower values of HRV [SDNN (73.8 ±21.1 ms vs. 164.9 ±38.1 ms), SDANN (62.2 ±19.0 ms vs. 139.5 ±33.3 ms)] compared to patients with moderate PH (p=0.0001 for all). SDNN inversely correlated with ratio of PAP/SAP of PH patients without shunt (r=-0.82; p=0.0002). Eisenmenger patients showed no significant difference of HRV [SDNN 157.6 ±43.2 ms, SDANN 141.2 ±45.3 ms] compared to patients with moderate PH without shunt (p >0.05 for all). CONCLUSIONS: According to our results, children with severe PH may have alterations in HRV. Since HRV appears to be related to disease severity, it may therefore serve as an additional diagnostic marker of PH. Remarkably, although Eisenmenger patients have suprasystemic pulmonary arterial pressures, they seem to have preserved HRV, which might reflect a more favourable autonomic adaptation.